ITRAQ‐Based Quantitative Proteomic Analyses of High Grade Esophageal Squamous Intraepithelial Neoplasia. Issue 11 (25th September 2017) - Zhang, Jingjing; Zhi, Chunchun; Zhen, Fuxi; Yuan, Xiaoqin; Jiao, Chunhua; Zhu, Hong; Zhu, Hui; Feng, Yadong
Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common cancers worldwide and is the fourth most lethal cancer in China. Little is known about the proteome of high grade esophageal squamous intraepithelial neoplasia (HGN), which is a premalignant lesion of ESCC. A quantitative proteomic analysis using an isobaric tag for relative and absolute quantification (iTRAQ) approach is used to characterize the protein expression profiles in HGN. Among the 3156 identified proteins, a total of 236 proteins are discovered to be differentially expressed. Compared with paired normal esophageal epithelial tissues, 138 proteins are upregulated and 98 proteins are downregulated in HGN. Bioinformatics analyses are performed according to gene ontology, clusters of orthologous groups, and kyoto encyclopedia of genes and genomes enrichment analyses. Six differentially expressed proteins are chosen and validated by Western blotting. The results of the study increase our understanding of early tumorigenesis during ESCC, and provide insights into the proteome at the initial stages of the disease that can be used to identify potential biomarkers for early diagnosis and for therapeutic targets.